1995
DOI: 10.1159/000109780
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Gait Changes in the Elderly: Pathological or Physiological?

Abstract: Aim: To examine the role of disease-related factors and age-related physiological changes in affecting gait speed and stride length in the elderly. Subjects: 925 men and 890 women aged 70 years and above who were ambulant, recruited by random sampling stratified according to age and sex, from all recipients of Old Age and Disability Allowance in Hong Kong. Design: Gait was assessed by measuring the time taken the number of steps required to complete a 16-foot walk. Information on health functional status cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 14 publications
3
33
0
7
Order By: Relevance
“…In another cohort of highfunctioning men and women aged 70-79 years, Seeman et al [2] showed that declines in physical performance (including measures of neurological function) were predicted by older age, lower income, higher education, relative weight and blood pressure, lower peak expiratory flow, diabetes, and other health conditions and hospitalizations. Some investigators [22,23], but not all [24], have found a relationship between increased frequency of falling and neurological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In another cohort of highfunctioning men and women aged 70-79 years, Seeman et al [2] showed that declines in physical performance (including measures of neurological function) were predicted by older age, lower income, higher education, relative weight and blood pressure, lower peak expiratory flow, diabetes, and other health conditions and hospitalizations. Some investigators [22,23], but not all [24], have found a relationship between increased frequency of falling and neurological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Gait changes associated with aging include decreased gait speed, decreased stride length, increased double support time, and increased width of the base of support (Woo et al 1995;Dobbs et al 1993;Elble et al 1991). These changes are more pronounced in individuals who are fearful of falling (Chamberlin et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although back pain is often reported as a consequence of osteoporosis, its prevalence in this population is not established. Furthermore, while there is some evidence to suggest that back pain influences balance [6,7] and functional mobility [8] in other populations, the effects of back pain have not been examined previously in individuals with osteoporosis. Studies [6,7] examining the effects of pain on balance have found that adults with chronic low back pain had greater standing postural sway compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Increased postural sway has been associated with the propensity to fall [9]. Woo et al [8] also found that increased back pain is associated with reduced gait speed in older adults without osteoporosis.…”
Section: Introductionmentioning
confidence: 99%